Looking for lovely : collecting the moments that matter - Downs, Annie F., 1980- (B & H Books, 2016)
Intensely personal, yet incredibly powerful, this book will spark transformative conversations and life changing patterns. No matter who we are and what path God has us on, we all need to look for lovely, fight to finish, and find beautiful in our every day!